(untitled) - Leach, James A. (Dubuque, IA, 2007)
AutoCAD 2007 Instructor is intended for instructor-lead instruction and self-instruction in AutoCAD software. AutoCAD is the market leader for all CAD software and is used by nearly two million students and professionals in architecture, engineering, construction, and design. AutoCAD 2007 Instructor makes it easy to upgrade from previous versions of AutoCAD by the use of a 2007 bar in the margin that highlights the new features.
Keywords: Computer graphics,Đồ họa máy tính